Variable rate technology fertilizer applicator for oil palm plantation - Ishola, Tajudeen Abiodun; Yahya, Azmi; Mohamed Shariff, Abdul Rashid; Abd Aziz, Samsuzana (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Currently, in the Malaysian oil palm plantation, fertilizer is applied manually or mechanically at uniform rate without due consideration to nutrient variability. Excessive application of this fertilizer contaminates ground water and raises its mineral contents above WHO limit for safe drinking water. However, Variable Rate Technology (VRT) fertilizer applicator promotes reduction in excessive fertilizer application, land degradation and pollution through leaching and volitization. A VRT fertilizer applicator for band application of granular fertilizer on tree crop was designed, developed and tested. Using RFID reader and LabVIEW computer program, the VRT fertilizer applicator detects the RFID code of the tag on each tree, relates the information to the database and triggers the control system to discharge the right amount of fertilizer to the required tree. The distribution uniformity test resulted in Coefficient of Variation (CV) range between 6.51 and 10.94 %. The VRT applicator has a field capacity of 7.22 ha/h and 7.71 ha/h with field efficiencies of 0.54 and 0.52 at the travelling speed of 4.43 km/h and 4.92 km/h, respectively. It is expected that the use of RFID technology will serve as alternative for tree crops where tree canopy has hindered proper application of GPS-based precision agriculture practices.